Transformation of Gotong Royong Values in Urban Communities in Fostering Attitudes of Responsibility and Social Care - GIRIMBANG WAHYU PRASETYO; YASNITA; YUYUS KARDIMAN (Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to analyze the transformation of mutual cooperation values in urban communities in fostering a sense of responsibility and social awareness through the presence of the Turun Tangan Jakarta Community. This study uses a qualitative approach with a phenomenological method. Primary data sources include key informants and informants comprising community coordinators, administrators, volunteers, and beneficiary residents. Secondary data sources were obtained through references such as journal articles, books, and so on. Data collection techniques were carried out through observation, interviews, and documentation. Data validity calibration techniques were carried out through persistent observation, data triangulation, and expert opinion. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The research findings show that the transformation of mutual cooperation values in urban communities is manifested in the form of new social practices that are adaptive to the characteristics of urban communities. These practices are implemented through approaches, the formation and implementation of service-based programs, cross-sector collaboration, as well as training and internal division of labor within the community.